Speech disfluencies in typically developing Finnish-speaking children - preliminary results - E. Jansson-Verkasalo; M. Silvén; I Lehtiö; K. Eggers (TAYLOR & FRANCIS INC, 2025)
We investigated the speech disfluencies of 54 typically fluent Finnish-speaking children: 14 children randomly selected from a longitudinal study (age levels 2, 3, and 4 years), and 40 children from a cross-sectional study (age levels 6, 7, 8, and 9 years). Speech samples, collected during a semi-structured conversation, were analysed for disfluencies per 100 words and 100 syllables. No significant within-age effect was found for the total frequency of disfluencies or disfluency types among the 2- to 4-year-olds. Across the 6- to 9-year-olds, between-group differences were found for the total frequency and type of disfluencies. Clinically relevant was that the criterion to distinguish normally fluent children from those who stutter, i.e., <3 stuttering-like disfluencies (SLD) per 100 syllables, was applicable in all age groups whereas the criterion <3SLD per 100 words was not. Consequently, these preliminary results suggest that different guidelines are needed for defining normal disfluency from stuttering in different languages.